Correlación y Regresión Lineal de la evaluación tiempo y puntaje con recurso interactivo Flash - Díaz Pinzón, Jorge Enrique (2017)
Flash interactive resources are a didactic resource of learning, in this case of sums of natural numbers. In this research work was established if there is a correlation between the times and score variables, with the application of the game Mobile targets -Sum. A study was carried out with 40 sixth grade students from General Santander IE in Soacha-Cundinamarca. The result reflected acorrelation between time and score (R =, 951), which is positive, is there is a directly proportional relationship between the variables